2007
DOI: 10.1097/01.ccm.0000281858.44387.a2
|View full text |Cite
|
Sign up to set email alerts
|

Liver proteomics for therapeutic drug discovery: Inhibition of the cyclophilin receptor CD147 attenuates sepsis-induced acute renal failure*

Abstract: Objective-Sepsis-induced multi-organ failure continues to have a high mortality. The liver is an organ central to the disease pathogenesis. The objective of this study was to identify the liver proteins that change in abundance with sepsis and, therefore, identify new drug targets. Design-Proteomic discovery study and drug target validation Setting-Research institute laboratorySubjects-Three month old C57BL/6 mice Interventions-We used a mouse model of sepsis based on cecal ligation and puncture (CLP) but with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Blocking the cyclophilinBsg interaction pharmacologically or by means of an antibody reduces the inflammation responses in a LPS-induced acute lung injury model and a bronchial asthma model in mice. 28,40 Dear et al 41 found that cyclophilin is upregulated in the liver in a sepsis model, and inhibition of Bsg attenuates sepsis-induced AKI. The numbers of labeled (adopted) neutrophils infiltrated into the kidneys after ischemia/reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Blocking the cyclophilinBsg interaction pharmacologically or by means of an antibody reduces the inflammation responses in a LPS-induced acute lung injury model and a bronchial asthma model in mice. 28,40 Dear et al 41 found that cyclophilin is upregulated in the liver in a sepsis model, and inhibition of Bsg attenuates sepsis-induced AKI. The numbers of labeled (adopted) neutrophils infiltrated into the kidneys after ischemia/reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis increases pro-and anti-inflammatory cytokines; the balance between pro-and anti-inflammatory cytokines is associated with severity of sepsis (10, 36, 41, 46, 49). Our group previously reported increases in proinflammatory cytokines TNF-␣ and IL-6 (4, 15, 54, 55) and an anti-inflammatory cytokine IL-10 in our CLP model (3,5,54). Therefore, we determined the therapeutic window for M2AA treatment to reduce CLP-induced increases in the proinflammatory cytokines TNF-␣, IL-6, and IFN-␥ (Fig.…”
Section: B-g and 2)mentioning
confidence: 99%
“…CLP was performed as previously described with some modifications (5,33). Our group (5) has previously reported, as have others (23), that the length of the ligated cecum determines the severity of sepsis and, ultimately, survival, kidney dysfunction (33), and liver damage (3)(4)(5). In this study, we ligated the cecum at 12 mm to obtain a model of moderately severe sepsis.…”
Section: Animalsmentioning
confidence: 99%
“…The urinary CypA concentration was determined by Western blotting, as previously described (22). The team member performing the Western blotting was blinded to which of the four groups the urine sample belonged.…”
Section: Human Studiesmentioning
confidence: 99%
“…CD147 is a receptor that mediates the actions of extracellular CypA [e.g., an anti-CD147 Ab completely prevents CypA-induced chemotaxis of neutrophils (15)]. In vivo, inhibition of CD147 reduces allergic inflammation in mouse models of asthma (14), collagen-induced arthritis (21), and sepsis-induced acute kidney injury (22). Although these in vivo effects have been attributed to CypA antagonism, there are other ligands that activate CD147, such as E-selectin (23).…”
mentioning
confidence: 99%